The Role of B and T Lymphocyte Attenuator in Respiratory System Diseases - Deng, Zheng; Zheng, Yi; Cai, Pei; Zheng, Zheng (Frontiers in Immunology, 2021)
B and T lymphocyte attenuator (BTLA), an immunomodulatory molecule widely expressed on the surface of immune cells, can influence various signaling pathways and negatively regulate the activation and proliferation of immune cells by binding to its ligand herpes virus entry mediator (HVEM). BTLA plays an important role in immunoregulation and is involved in the pathogenesis of various respiratory diseases, including airway inflammation, asthma, infection, pneumonia, acute respiratory distress syndrome and lung cancer. In recent years, some studies have found that BTLA also has played a positive regulatory effect on immunity system in the occurrence and development of respiratory diseases. Since severe pulmonary infection is a risk factor for sepsis, this review also summarized the new findings on the role of BTLA in sepsis.